Pelaksanaan Sistem Informasi Manajemen dalam Pengambilan Keputusan pada Kantor Kecamatan Baranti Kabupaten Sidenreng Rappang - Akhmad Sahrah (FISIP Universitas Muhammadiyah Sidenreng Rappang, 2013)
Abstract Advances in information technology had been expected to assist in the processing and preparation of information quickly and accurately in order to support the decision-making process. Therefore this study was aimed to determine the implementation of management information systems in decision making at Baranti District Office in Sidenreng Rappang Regency. This research was a descriptive quantitative type, held at Baranti District Office. The population was the entire employees as many as thirty (30) people, and all of them were accounted as sample. Datas were collected through observation, interviews, and questionnaires. The results showed that the implementation of management information systems in decision making at Baranti District Office in Sidenreng Rappang went well, judging from the data collection was good (63,33%), as well as the classification and processing of the data (70%). While the affecting factors, namely District Head’s leadership was good (50%), poor support facilities (56.66%), and unfavorable human resources (63,34%).